A role for annexin A2 in scaffolding the peroxiredoxin 2-STAT3 redox relay complex - Talwar, Deepti; Messens, Joris; Dick, Tobias P. (Nature Communications, 2020)
Hydrogen peroxide (H2O2) is recognized to act as a signaling molecule. Peroxiredoxins (Prxs) have the ability to transfer H2O2-derived oxidizing equivalents to redox-regulated target proteins, thus facilitating the transmission of H2O2 signals. It has remained unclear how Prxs and their target proteins are brought together to allow for target-specific protein thiol oxidation. Addressing the specific case of Prx2-dependent STAT3 oxidation, we here show that the association of the two proteins occurs prior to Prx oxidation and depends on a scaffolding protein, the membrane chaperone annexin A2. Deletion or depletion of annexin A2 interrupts the transfer of oxidizing equivalents from Prx2 to STAT3, which is observed to take place on membranes. These findings support the notion that the Prx2-STAT3 redox relay is part of a highly organized membrane signaling domain.
Gesehen am 12.02.2021